(untitled) (PANGEEA, 2025)
Rural communities in the Apuseni Mountains. Avram Iancu village. Apuseni Mountains community problems were early on in Romanian rural sociology, a perpetual object of the studio. For knowledge about the geographic (location, boundaries, neighborhood, terrain, geology, climate, water, vegetation, fauna and soil), demographic (spatial locality development, population and settlements) and economic (geo-economic function, tourist) in 2007 started a comprehensive study on the settlements situated on the river Arieş and Arieşul Mic, the perimeter area Avram Iancu - Bistra. In this paper we propose to present the main aspects of economic and social geographical Avram Iancu.